Positives approaches: new empirical research in accounting (1991)
The contemporary debates of the accountancy discipline can be framed on the normative and positive approaches developed by researchers as: Mattessich, Ijiri, Zirnmerman, etc. This article attemps to organize in a systematic way the trends of the so called new empiric research in the positive accounting theory structure. The newempiric research undertakes a complex theoretical and experimental framework in the trends of the so called accounting aggregate market as well as the trend called accounting behavior.